2019
DOI: 10.3390/en12030572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Disc Tip Geometry on the Aerodynamic Performance and Flow Characteristics of Multichannel Tesla Turbines

Abstract: As a competitive small-scale turbomachinery option, Tesla turbines have wide potential in various fields, such as renewable energy generation systems and small power equipment. This paper investigates the influence of disc tip geometry, including its profile and relative height, on the aerodynamic performance and flow characteristics of one-to-one and one-to-many multichannel Tesla turbines. The results indicate that compared to the turbine with blunt tips, the isentropic efficiency of the one-to-one turbine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
10
0
3
Order By: Relevance
“…It has been found that the tangential velocity in the core region is less for contrarotating disks than for corotating disks. 42 Accordingly, the core temperature is more for corotating disks than contrarotating disks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the tangential velocity in the core region is less for contrarotating disks than for corotating disks. 42 Accordingly, the core temperature is more for corotating disks than contrarotating disks.…”
Section: Resultsmentioning
confidence: 99%
“…Fluid flows between two heated concentric rotating disks 42 as shown in (Figure 1A and 1B). Figure 1C shows an axisymmetric computational domain where the angular speeds of the top disk and the bottom disk are ω 1 and ω 2 , respectively, and the gap between the disks is L. Fluid enters the peripheral gap and discharges at the inner radius r i .…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get P01, Equation ( 4) from [10] can be used, and ¨P can be calculated as stated in this article [11]. Noted that the efficiency of the turbine decreases with the increase in rotational speed [12]. Where: P01 = H = total head P = pressure ȡ = density g = gravity V = velocity z = elevation (5) Where: ¨P = head loss ¨Pin = head loss at inlet ¨Pout = head loss at outlet ( 6 ) Where: ¨Pin = head loss at inlet ‫ܭ‬ = area ratio Vin = velocity at inlet g = gravity ( 7 ) Where: P01 = H = total head P = pressure ȡ = density g = gravity V = velocity z = elevation ( 8 ) Where: ‫ܭ‬ = area ratio An,i = cross-sectional area at nozzle inlet An,o = cross-sectional area at nozzle outlet…”
Section: Efficiencymentioning
confidence: 99%
“…The predicted efficiency of turbine oscillates around 50%. Rusin et al [8] compared the experimental results of Tesla turbine with numerical analysis by considering the surface roughness of the disks. The highest power and efficiency values obtained were: 55.6 W, 11.2% for inlet pressure 3 bar and 98.3 W, 11.8% for 4 bar.…”
Section: Introductionmentioning
confidence: 99%